Zeolites surface reactions pointed out by charge parameters - Torres Sanchez, Rosa Maria (2001)
The diffusion potential technique was applied to determine the isoelectric point (IEP) of solid samples taken after different reaction times in two selected zeolite hydrothermal transformations (1). NaA to HS and (2) NaY to NaP. Both reactions were also followed by X-ray diffraction analysis of the solid phase. Experiments included the study of solids consisting of different starting and final proportions of the phases. Differences were found between the IEP values obtained for these samples and those of corresponding mechanical mixtures of NaArHS and NaY/NaP, prepared to the same composition. It was established that both transformations began onto the starting NaA and NaY zeolite surfaces, the final zeolite cover, and in some extent the surface of the former.